Potret pendidikan pemakai selama pandemi Covid-19: Studi kasus pada UPT Perpustakaan dan Universitas Diponegoro Press - Nabilla Layza Nugroho; Roro Isyawati Permata Ganggi (Prodi S1 Ilmu Perpustakaan dan Informasi, Fakultas Ilmu Budaya, Universitas Diponegoro, 2025)
[Title: a Portrait of User Education During The Covid-19 Pandemic: A Case Study Of Technical Executive Unit Library and Press Universitas Diponegoro] The background of this research is that sometimes there are students who know where to find the right reference for their assignment, and there are students who have problems finding references. Therefore, the Technical Executive Unit Library and Press Universitas Diponegoro organized a